6-methoxyquercetin-3-0-(6-E-feruloyl)-beta-D-glucopyranoside from Paepalanthus polyanthus (Eriocaulaceae) - dos Santos, L. C.; Piacente, S.; Pizza, C.; Toro, R.; Sano, P. T.; Vilegas, Wagner [UNESP] (Elsevier B.V., 2002)
The new 6-methoxyquercetin-3-O-(6-E-feruloyl)-beta-D-glucopyranoside (1) was isolated from the aerial parts of Paepalanthus polyanthus and characterized by spectroscopic methods, mainly 1D and 2D NMR experiments, as well as electrospray mass spectrometry. In addition four known flavonoids of taxonomic relevance were isolated and identified by comparison to literature data. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: Paepalanthus; sect. Actinocephalus; eriocaulaceac; acyl glycosylated flavonoids; chemotaxonomy; 6-methoxyquercetin-3-0-(6-E-feruloyl)-beta-D-glucopyranoside